Kukupu Dance Learning Innovation: Using Pop-Up Book Media to Improve Elementary School Students' Knowledge - Amelia, Mesa; Sunaryo, Ayo; Badaruddin, Saian; Anizaim, Aimi Nabila (Universitas Pendidikan Indonesia, 2025)
This study examines the effectiveness of using pop-up books in learning the Kukupu dance as an effort to improve dance knowledge in elementary school students. The Kukupu dance, which is part of cultural heritage, requires a deep understanding of movement techniques and the accompanying cultural context. The use of pop-up books as a learning medium was chosen because of its advantages in presenting information visually and interactively, making it easier for students to understand complex concepts. The research methodology involved designing pop-up books that integrate key elements of the Kukupu dance, such as movements, costumes, and cultural background, and implementing them in classroom learning activities. The research subjects consisted of fourth and fifth grade elementary school students, with the evaluation process carried out through observation, interviews, and knowledge tests before and after the media application. The analysis results showed that the use of pop-up books significantly improved students' dance knowledge, with a clear increase in understanding of movement techniques, costumes, and the cultural context of the Kukupu dance. These findings confirm the potential of pop-up books as an effective tool in dance learning, offering an innovative alternative to increase student engagement and understanding at the elementary school level.